GENDER IN CULTURAL COMMUNICATION - Evi Novianti; Aat R. Nugraha (Metakom, 2018)
Choose the way as a DJ began to take many people because the existence of his music seemed to grow and never fade. Actually have work related to this, there is no harm as long as a DJ has points that must be met in order to still exist. The job is in demand by women. The method used is qualitative with dramaturgy approach. There is uniqueness in a Dj. Popular culture deals with everyday issues that can be enjoyed by all people or certain circles such as mega stars, private vehicles, fashions, home models, body treatments and so on. Self presentations include manipulation of fashion symbols, body language, make over, message content, language style. Keywords: Disk Jockey, the exixtence of music, culture, women